If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-1x) = x + 9 Remove parenthesis around (-1x) 2 * -1x = x + 9 Multiply 2 * -1 -2x = x + 9 Reorder the terms: -2x = 9 + x Solving -2x = 9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2x + -1x = 9 + x + -1x Combine like terms: -2x + -1x = -3x -3x = 9 + x + -1x Combine like terms: x + -1x = 0 -3x = 9 + 0 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| 220-6w=-80 | | X+y+6z=84 | | 8=15-z | | 24x+14=86 | | 0.4x-0.1=0.3x+2 | | 81=87-x | | 1+3=(-3)+3+1+x | | 40+y=32 | | 8k+8+2-k= | | 12d^2-71d-6=0 | | Y-4x=5xy+7 | | -2(2x-8)=-20 | | 1/5(9t-4)=t+4/10 | | 7K+2=23 | | 4(-10-5x)=-160 | | 14-32=-6X | | 6x+12=78 | | -8+2x=-24+12x | | 3[6-(-8x-3)]=168x+81 | | 2+2x=-20 | | 4p^2+9=12p | | 2(10+3x)=26 | | 106-48=x | | 2(10+3x)=/6 | | 54-3x=6-9x | | -8n+2(12n+11)=-5+5(n+12) | | y^2-4z^2-2y=0 | | 2(-4+4x)=80 | | 7x+10x=105 | | f(6)=4x+5 | | 8+3x-2=12 | | 3+9x=-45+x |